2010
DOI: 10.1002/j.2161-1912.2010.tb00117.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Acculturation and Enculturation on Mexican American High School Students' Decision to Apply to College

Abstract: This study examined the influence of acculturation, enculturation, parental education level, financial concerns, and gender on 106 Mexican American high school students' decisions to apply to college. Results indicated that acculturation and female gender were significant predictors. Implications for interventions with Latino high school students are discussed.Este estudio examinó la influencia de la aculturación, la enculturación, el nivel de educación de los padres, las preocupaciones financieras y el sexo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…Higher scores on the Anglo Orientation subscale (AOS) indicate higher acculturation to the White culture, whereas higher scores on the Mexican Orientation subscale (MOS) represent higher enculturation to the Mexican culture. Reliability estimates range from .73 to .79 on the AOS and .91 on the MOS (Bauman, ; Castillo, Lopez‐Arenas, & Saldivar, ). For the current study, Cronbach's alpha was .63 for the AOS and .93 for the MOS.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores on the Anglo Orientation subscale (AOS) indicate higher acculturation to the White culture, whereas higher scores on the Mexican Orientation subscale (MOS) represent higher enculturation to the Mexican culture. Reliability estimates range from .73 to .79 on the AOS and .91 on the MOS (Bauman, ; Castillo, Lopez‐Arenas, & Saldivar, ). For the current study, Cronbach's alpha was .63 for the AOS and .93 for the MOS.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores on Mexican orientation represent stronger levels of enculturation to the Mexican culture. Reliability estimates range from .75 to .91 on the Mexican Orientation subscale (Bauman, 2005; Castillo et al, 2010; Vela, Johnson, et al, 2014). For the current study, Cronbach’s alpha was .93 for the Mexican Orientation subscale.…”
Section: Methodsmentioning
confidence: 99%
“…However, they believed that negative experiences within a new culture, individual factors (e.g., ethnic identity, coping), and family processes (e.g., parental expectations) might influence the relationship between acculturation and mental health. In another study, Castillo, López‐Arenas, and Saldivar (2010) examined Mexican American adolescents’ decision to apply to college, with acculturation, enculturation, parental education level, financial concerns, and gender as predictor variables. Results showed that acculturation to American culture and gender (female) predicted students’ decision to apply to college.…”
Section: Family and Cultural Factorsmentioning
confidence: 99%
“…For example, cultural factors due to generation location (i.e., 1st generation, 2nd generation immigrant; 1.5 generation being minors who immigrate with their parents, see Farley & Alba, 2002) may play a vital role in post-secondary enrollment and persistence. For example, previous research indicates that those adolescents who are more acculturated exhibited greater tendencies both with respect to pursuing and persisting in post-secondary education (Castillo, López-Arenas, & Saldivar, 2010; see also Flores, Ojeda, Huang, Gee, & Lee, 2006).…”
Section: Acculturationmentioning
confidence: 99%